Clarification of the identity of Helicina mediana Gassies, 1870 from New Caledonia (Gastropoda, Neritimorpha, Helicinidae) - Richling, Ira (Zootaxa, 2017)
The identity of Helicina mediana Gassies, 1870 was clarified by the study of the type material and the selection of a lectotype. It is currently classified as Sturanya mediana (Gassies, 1870) and replaces the temporarily applied name Sturanya novaecaledoniae (Baird, 1873) for the medium sized helicinid species widely spread in the north-eastern part of mainland New Caledonia and the adjacent Îles Belep. The latter name and Helicina nehoueensis Hartman 1889 are synonyms of S. mediana.